Crossing Lines in GSG - Reis, J. (Proceedings of the International Conference on Information Systems and Design of Communication, 2014)
Based on the previous and ongoing work of the development of GSG, an extensible expert system shell tool to support creative work involving shape computing with Shape Grammars, this paper shows an evolution and refinement of the system. A refined class structure and the line intersections types appropriate for matching shapes in the process of shape grammar rule application are presented. Operations for the algebras of shapes (which are essential in the mechanics of the application of rules in shape computing) are discussed, for both maximal and non maximal shapes. In particular, details and tests of the implementation of these operations for the maximal case are also shown.